PEMBINAAN PEMELIHARAAN BANGUNAN DRAINASE BAGI MASYARAKAT DESA SRIKUNCORO KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Besperi Besperi; Makmun R. Razali; Samsul Bahri (DHARMA RAFLESIA, 2018)
Indonesia has 2 seasons, rainy season and wet season. Normally, it will be flooding in the rainy season in Bengkulu mosely in Central Bengkulu. Flooding happens every year, and this problem does not have the solution yet and the fread shows the increase in frequency, the areas, the depth and the duration. Central Bengkulu has bad drainage. No bad condition of the road, its dishersing the activity of the society. It is imposible to wait for the action from the government to overcome this situation. The society pay great attention from the speech and discusstion about the method to make drainage based on standard. Keywords: Flood, Drainage Contruction, Government and Stakeholders